Hubungan Penggunaan Media Sosial pada Orangtua dengan Pola Makan Anak TK Al Ikhlas Kecamatan Arjasa Kangean - Yura Melly Safira (Universitas Airlangga, 2023)
Background: Preschool age is a child aged 3-6 years. At this age, children have a higher ability to grow and develop. Providing stimulation and a good diet for children will be beneficial for the child's growth and development process. Preschool-age children are very large in Indonesia, namely 20% of the total population, in the age range of 36 months to 5 years. Objectives: This study aims to determine the relationship between social media use by parents and children's eating patterns at TK Al Ikhlas, Arjasa Kangean District. Methods: This study used quantitative observational research. This research was conducted using a cross-sectional study design. Samples were taken using a proportional random sampling technique from 83 mothers of kindergarten children. Results: There is no relationship between the frequency of social media use and children's eating patterns (pv=0.218), and there is no relationship between the frequency of social media use and parenting styles of children (pv=0.121). Conclusions: There is a relationship between the use of social media by parents and the eating patterns of children in TK Al Ikhlas, Arjasa Kangean District. This happens because parents' use of social media is relatively short, so parents can still give their full attention to their children.